2014
DOI: 10.5713/ajas.2013.13770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particular Breed on the Chemical Composition, Texture, Color, and Sensorial Characteristics of Dry-cured Ham

Abstract: The present study demonstrates the impact of specific breed on the characteristics of dry-cured ham. Eighty thighs from Korean native pig (KNP), crossbreed (Landrace×Yorkshire)♀×Duroc♂ (LYD), Berkshire (Ber), and Duroc (Du) pig breeds (n = 10 for each breed) were used for processing of dry-cured ham. The thighs were salted with 6% NaCl (w/w) and 100 ppm NaNO2, and total processing time was 413 days. The effects of breed on the physicochemical composition, texture, color and sensory characteristics were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
3
17
3
Order By: Relevance
“…Similarly, the replacement with 2% GP did not affect the protein content within any product studied. The protein contents ranging between the products from 32.33 g/100 g to 38.85 g/100 g in the present study were lower than the levels (40-42 g/100 g) reported for dry-cured hams in literature (Marusic et al 2011;Seong et al 2014). The contrasting results could be explained by lower moisture contents in samples in these studies.…”
Section: Resultscontrasting
confidence: 57%
See 4 more Smart Citations
“…Similarly, the replacement with 2% GP did not affect the protein content within any product studied. The protein contents ranging between the products from 32.33 g/100 g to 38.85 g/100 g in the present study were lower than the levels (40-42 g/100 g) reported for dry-cured hams in literature (Marusic et al 2011;Seong et al 2014). The contrasting results could be explained by lower moisture contents in samples in these studies.…”
Section: Resultscontrasting
confidence: 57%
“…Comparing the a w values between the cut products shows significantly lower values in Boseop at all replaced levels as compared with those of the other products (P < 0.05). The a w values in all samples made with/ without GP in the present study were generally lower than the values (0.89-0.91) reported for dry-cured ham ripened for 413 days (Seong et al 2014), but almost similar to the values (0.86-0.88) reported of dry-cured ham ripened for 415 days (Andres et al 2005). The contrasting results could be due to the difference between the studies in the sizes of raw materials or ripening conditions used.…”
Section: Resultscontrasting
confidence: 50%
See 3 more Smart Citations